2013
DOI: 10.1111/evo.12076
|View full text |Cite
|
Sign up to set email alerts
|

Sperm Competitive Ability Evolves in Response to Experimental Alteration of Operational Sex Ratio

Abstract: In naturally polygamous organisms such as Drosophila, sperm competitive ability is one of the most important components of male fitness and is expected to evolve in response to varying degrees of male-male competition. Several studies have documented the existence of ample genetic variation in sperm competitive ability of males. However, many experimental evolution studies have found sperm competitive ability to be unresponsive to selection. Even direct selection for increased sperm competitive ability has fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 56 publications
6
65
1
Order By: Relevance
“…Intensity of interlocus conflict is expected to be high under male biased condition, moderate under equal sex ratio and low under female biased regime. Evolution of sperm competitive ability in these selection regimes has already been reported [37]. We have shown that both components of sperm competitive ability (i.e., offense and defense) have declined under F-regime, while sperm defense has increased under M-regime [37].…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Intensity of interlocus conflict is expected to be high under male biased condition, moderate under equal sex ratio and low under female biased regime. Evolution of sperm competitive ability in these selection regimes has already been reported [37]. We have shown that both components of sperm competitive ability (i.e., offense and defense) have declined under F-regime, while sperm defense has increased under M-regime [37].…”
Section: Introductionmentioning
confidence: 78%
“…The mechanism by which males cause increased mate-harm could be chemical (more toxic ejaculate) or physical (higher amount of courtship). At this point it is difficult to predict whether increase in mate-harming abilities of M-males is due to the evolution of behavioural components or due to the evolution of the ejaculate [37]. Increase in courtship frequency (discussed above) in M-males is an indication of changes in the physical component of mate-harm [6,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of the three independent replicates of the female-biased regime (F 1,2,3 ) and the male-biased regime (M 1,2,3 ) were created by altering the sex ratio to female biased (1 male: 3 female) and male biased (3 male: 1 female) respectively 24 . All assays were done between the 95 th and 105 th generations of selection.…”
Section: Resultsmentioning
confidence: 99%
“…The LHst females were generated by collecting eggs from the LHst base population at a density of 70 eggs per vial and incubating the vials containing standard cornmeal-molasses-yeast food at standard laboratory conditions [43]. The flies started eclosing by 9th day post egg collection with peak eclosion on 10th day post egg collection.…”
Section: Methodsmentioning
confidence: 99%